Blended Finance : A Stepping Stone to Creating Markets - Sierra-Escalante, Kruskaia (International Finance Corporation, Washington, DC, 2018)
At the heart of International Finance Corporation’s (IFC’s) approach to blended finance are efforts to create and help sustain private markets with strong development impact. This note explores the role of blended finance in creating markets and looks at lessons from three blended finance projects and structures - and how each contributed to the creation of markets that are scalable, sustainable, and resilient. The projects illustrate the value of using blended finance to kick-start markets and to push to achieve long-term financing on commercial terms. They also carry important lessons for using and scaling up blended finance in the future.